Diagnostic value of Johnson & Dare's methods in estimating the birth weight using the Rock curve - Elham Azmoudeh; Somayeh Alirezaei; Habibollah Esmaily (Mashhad University of Medical Sciences, 2018)
Introduction:Fetal weight is an important criterion for assessing the neonate's health and taking clinical decisions. Johnson and Dare's formula are the methods for estimation of fetal birth weight which are less used. This study was performed with aim to determine the diagnostic value of Johnson & Dare's methods in estimating the birth weight using the Rock curve. Methods:This cross-sectional study was performed on 147 full-term, cephalic, singleton pregnancies in the maternity of Nohon Dey and Taamin Ejtemaei hospitals of Torbat Heydariyeh in 2016. Before birth, Johnson and Dare formula was used to calculate fetal weight. After birth, all infants were weighed and then the true weight of infants was compared with the estimated weights. Data analysis was done with SPSS software (version 20) and by Kruskal-Wallis test, specificity and sensitivity formula, positive & negative predictive value. P<0.05 was considered statistically significant. Results: There was no significant difference between Johnson & Dare methods with actual birth (P>0.05). The sensitivity of Johnson formula for estimation of fetal low birth weight and normal fetuses was 60% and for macrosomic fetuses was 71.43%. The sensitivity of Dare formula for estimation of fetal low birth weight and normal fetuses was 40% and for macrosomic fetuses was 85.71%. The area under the curve in the predictive model for two methods and in three weight groups of <2500 g (p=0.26), 2500-4000 g (p=0.26) and >4000 g (p=0.13) had no significant difference. Conclusion:Johnson and Dare formula in estimation of fetal weight especially in macrosomic fetuses can be good replacement for costly methods such as sonography. Also, Dare method can be used more than before in estimation of fetal weight because it is easy, fast and accurate.